The Effect of 'One Four' On The Knowledge and Attitudes of Women of Religious Age In Control of Non-Communicable Diseases (NCDs) - Fatmayanti, Aulia; Harwijayanti, Bekti Putri (Postgraduate Program , Poltekkes Kemenkes Semarang, 2025)
According to WHO, 77% of all deaths from NCDs and 85% of premature deaths occur in low- and middle-income countries. The main challenge in preventing and controlling NCDs is that the main drivers and risk factors including poverty, air pollution, lack of physical activity, and the marketing and sale of tobacco, alcohol, and processed foods are all outside the scope of control of government health departments or national health systems. The responsibility to address these underlying determinants lies with various government sectors and departments, such as education, labor, transportation, trade, finance, environment, agriculture, and manufacturing. NCDs in women have major implications, various complications during pregnancy, childbirth, and postpartum in mothers with NCDs trigger higher mortality and morbidity in mothers and children. This shows the need to initiate a program that integrates various parties in efforts to overcome NCDs in the community in the form of